PENINGKATAN LITERASI DIGITAL MELALUI SOSIALISASI AUGMENTED REALITY UNTUK MENDUKUNG PEMBELAJARAN BERBASIS VISUALISASI KAPAL - Dio, Rafi; Slam, Berta Erwin; Apriyenson, Hoki; Manik, Agustina Sartika Yos Ekaristi; Vivi , Putri Meylia; Nusyirwan, Deny; Nadeak, Yohanes E; Pane, Glenn Oriona; Tampubolon, Angel Debora; Aziis, Fauziah An Nisadiena; Epodius, Gabriel Alexander; Pasaribu, Tinawati Br; Manurung, Reyaldi Panorangan; Rizky, Muhammad; Nurhadi, Nurhadi (PUAN INDONESIA, 2025)
The rapid advancement of Information and Communication Technology (ICT) has significantly transformed educational practices by introducing innovative and interactive learning tools. One such technology is Augmented Reality (AR), which merges real-world environments with virtual elements in real-time, providing immersive and engaging educational experiences. This community service activity aimed to enhance digital literacy among teachers and students at SMKN 5 Tanjungpinang through the introduction and practical demonstration of AR as an interactive learning medium. The implementation involved presenting the basic concepts of AR, hands-on demonstrations using mobile-based AR applications featuring realistic 3D models of ships, and simulations of maritime conditions using AR models. These simulations allowed participants to explore vessel scenarios and behaviors in various sea conditions, thus bridging theoretical concepts with practical visualization. Evaluative feedback, gathered through interviews and direct observations, indicated that the AR sessions significantly improved participants' understanding of complex visual-spatial concepts inherent in maritime education. Participants also expressed high enthusiasm, suggesting strong acceptance and potential for broader integration of AR technologies in vocational education. This initiative underscores the importance of interactive and simulation-based technologies in education, particularly in technical fields requiring detailed visualization and practical comprehension. Keywords—Augmented Reality, Digital Literacy, Interactive Learning, Simulation, Maritime Education, Visualization